Determinant Factors which Related with Premature Birth - Ratu Kusuma; Suci Rahmani Nurita; Gustina; Maidawilis; Mitayani; Budhi Mulyadi (Talenta Publisher, 2025)
In 2023 Indonesian Health Survey reported that 0.6% of Indonesian women had their first pregnancy at ages 10-14, and 25.8% at ages 15-19. Medical records from the MCH Clinic at Putri Ayu Community Health Center in Jambi City stated around 164 adolescent pregnancies (ages 14-19) over the past five years (2020-2024), but only 120 births were recorded. This was a cross-sectional study using secondary data from the MCH Clinic and Independent Midwife Practices in the working area of Putri Ayu Community Health Center in Jambi City from January 01, 2020 to December 31, 2024. This study aims to analyse factors associated with premature births among adolescents in the working area of the Putri Ayu Community Health Centre in Jambi City. The study sample included all 120 pregnant adolescents (ages 14-19). Data were analysed using univariate, bivariate, and multivariate. Univariate analysis was presented as a frequency distribution, and bivariate analysis used a chi-square test to examine the relationship between all characteristic variables and premature birth. Multivariate analysis used logistic regression to determine which variable had the most significant influence on premature birth. The chi-square results indicated that all determinants (maternal age at pregnancy, maternal nutrition during pregnancy, frequency of antenatal care, and history of abortion) were significantly related to premature birth (p-value = 0.05). The logistic regression analysis showed that maternal age at pregnancy was the most dominant factor influencing premature birth, indicated by the highest odds ratio (OR = 7.034), while nutritional status was not statistically significant in relation to premature birth (p-value= 0.309). Keyword: Adolescent Pregnancy, Determinant Factors, Premature Birth